2006
DOI: 10.1152/ajplung.00045.2006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial aldehyde dehydrogenase attenuates hyperoxia-induced cell death through activation of ERK/MAPK and PI3K-Akt pathways in lung epithelial cells

Abstract: Oxygen toxicity is one of the major risk factors in the development of the chronic lung disease or bronchopulmonary dysplasia in premature infants. Using proteomic analysis, we discovered that mitochondrial aldehyde dehydrogenase (mtALDH or ALDH2) was downregulated in neonatal rat lung after hyperoxic exposure. To study the role of mtALDH in hyperoxic lung injury, we overexpressed mtALDH in human lung epithelial cells (A549) and found that mtALDH significantly reduced hyperoxia-induced cell death. Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 45 publications
1
57
1
1
Order By: Relevance
“…However, it has been reported that MST can both oxidize thioredoxin, a key intermediate in cellular redox reactions, and react with peroxides and that this may be a physiologically significant mechanism for combating oxidative challenges [41,42]. Recently, it has been reported that overexpression of ALDH-2 confers lung epithelial cell resistance to hyperoxia-induced cell death in part by reducing intracellular and mitochondrialderived ROS production [43]. Another mechanism by which ALDH-2 may function as an antioxidant involves lipid peroxidation-derived aldehydes (LP-DA).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that MST can both oxidize thioredoxin, a key intermediate in cellular redox reactions, and react with peroxides and that this may be a physiologically significant mechanism for combating oxidative challenges [41,42]. Recently, it has been reported that overexpression of ALDH-2 confers lung epithelial cell resistance to hyperoxia-induced cell death in part by reducing intracellular and mitochondrialderived ROS production [43]. Another mechanism by which ALDH-2 may function as an antioxidant involves lipid peroxidation-derived aldehydes (LP-DA).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Buckly et al concluded that the ERK-dependent pathway mediates its effects by protecting the basement membrane against hyperoxic DNA strand breakage and death of type II alveolar epithelial cells [52]. A recent study also demonstrates that activation of ERK1/2 induced by either exposure to hyperoxia or over-expression of mitochondrial aldehyde dehydrogenase (mtALDH) attenuates hyperoxia-induced non-apoptotic death of lung epithelial cells through compensatory AKT cell survival signaling pathways [53]. Inosine, a naturally occurring purine with anti-inflammatory properties, was shown to reduce hyperoxicinduced cell death of alveolar epithelium by increasing ERK1/2 activation [54].…”
Section: Expression Of Regulatory Genes In Hyperoxic Cell Deathmentioning
confidence: 99%
“…Several reports have suggested that polymorphism ALDH2 genes have a fundamental relationship with colorectal cancer, primary hepatocellular carcinoma, and stomach cancer [28][29][30][31] . More important, mitochondrial ALDH2 functions as a protector against oxidative stress [14,32,33] . Our subsequent research verified this viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are still needed to shed light on these relation ships [14,38] . In summary, this study provides evidence that overexpression of ALDH2 can protect PBMCs against H 2 O 2 -induced oxidative damage and attenuate apoptosis.…”
Section: Wwwchinapharcom Hu Xy Et Almentioning
confidence: 99%
See 1 more Smart Citation